Wieloznaczność poznawcza jako strategia komunikacyjna - Dobrosz-Michiewicz, Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The paper presents the results of empirical experimental research on the influence of ambiguity of communication on the message persuasive effect. The results obtained have led, in principle, to the following conclusions regarding cognitive ambiguity phenomena in communication:1) The higher the message ambiguity means the higher the consensus of the recipients with the communicated content; ambiguity in communication constitutes a specific inhibitor of audience opposition to communicated content.2) The rule above does not apply to communication in the case of previously polarized attitudes of the audience (ambiguity as a strategy of maintaining the status quo– with its help we will not be convinced until now, but we also do not discourage us).3) The limitation for the use of ambiguity as a communication strategy calculated on the persuasive effect is the coexistence of messages operating at different levels of ambiguity; The presence of a message that operates the ambiguity of the base level in the message weakens the effect of higher order ambiguity on the agreement reached by the persuasive message.4) Attitudes shaped by messages operating at a higher level of conceptualization of ambiguity are less resistant to change.